(untitled) (Revista de Ciências Agroveterinárias, 2017)
The pig farming has been highlighted globally over the last few years. In Brazil the production of swine deserves to be recognized in growth terms owed mainly the changes in the breeding systems. With the integration model, the producers started to have greater contribution and technical orientation, as well as a pre-established sale with the integrating company. As a result, swine production developed rapidly in three southern states (Paraná, Santa Catarina and Rio Grande do Sul) that have the largest swine herds in the country. This work had as an objective the current situation of piglets production units the northwestern region of Rio Grande do Sul the main items that make up the biosecurity program, identifying critical points and listing opportunities to improve the process.The adopted methodology consisted of the application of semi structured questionnaire and visiting the properties of the integrated producers. As a result, it was observed that (27.3%) of the farms produce Weaned Pigs, and (72.7%) are units producing pigs without day care. Regarding the enclosure, where 72.6% of the farms answered the question, another item was the access to water for animal watering, where 54.5% have access via an artesian well. Most of the units studied reached the objectives and standards of biosafety, thus guaranteeing the health and quality of the pork produced, but there were also opportunities for improvements in relation to some of the requirements, among which the enclosure, chlorination of water for Animal welfare, the location of treatment lagoons and aspects related to the discharge and loading of animals.